A Rare Case of Unruptured Small Aneurysm Arising from the Posterior Surface of Proximal A1 Segment, Projecting Posterior-Inferiorly and Entangled with Multiple Perforators from the A1 Segment - Kale, Samir Jagannath; Tanaka, Riki; Okubo, Mai; Sasaki, Kento; Miyatani, Kyosuke; Yamada, Yasuhiro; Komatsu, Fuminari; Kato, Yoko (Asian Journal of Neurosurgery, 2024)
Aneurysm arising from the A1 segment of the anterior cerebral artery is rare. Aneurysm of the A1 segment even being small tend to rupture early. They tend to develop along the with various vascular anomalies of the vessels arising from the A1 segment. Use of computational fluid dynamics and hemodynamic consideration is of importance in this aneurysm. In this report we describe a 57-year-old woman with a small, unruptured A1 segment aneurysm arising from the proximal segment of the posterior surface of A1, and pointing posterior-inferiorly with multiple perforators entangling around for which microsurgical clipping was done. Intraoperative clipping of the aneurysm and salvaging the multiple perforators were challenging. We report a rare case of an A1 segment aneurysm arising from the posterior surface facing with multiple perforators. It is of significance to understand that a small, unruptured A1 aneurysm can arise from the posterior surface of the A1 segment with projection posterior-inferiorly making it deeper in location with multiple perforators entangling it; hence, it is challenging to treat without causing neurological deficits.
Keywords: proximal A1 segment; posterior-inferiorly; perforators; computational fluid dynamics; motor-evoked potential (MEP)